Discovery and prospects of new heterocyclic Isatin-hydrazide derivative with a novel role as estrogen receptor α degrader in breast cancer cells - Arif, Muhammad Nouman; Sarwar, Sadia; Firdous, Farhat; Saleem, Rahman Shah Zaib; Nadeem, Humaira; Alamro, Abir Abdullah; Alghamdi, Amani Ahmad; Alshammari, Atekah Hazza; Farooq, Omer; Khan, Rashid Ali; Faisal, Amir (Frontiers in Chemistry, 2024)
Introduction: Isatin, a heterocycle scaffold, is the backbone of many anticancer drugs and has previously been reported to engage multiple cellular targets and mechanisms, including angiogenesis, cell cycle, checkpoint pathways and multiple kinases. Here, we report that a novel isatin derivative, 5i, degrades estrogen receptor alpha (ERα) in estrogen-dependent breast cancer cells. This effect of the isatin nucleus has not been previously reported. Tamoxifen and fulvestrant represent standard therapy options in estrogen-mediated disease but have their own limitations. Isatin-based triple angiokinase inhibitor BIBF1120 (Nintedanib) and multikinase inhibitor Sunitinib (Sutent) have been approved by the FDA. Methods: Keeping this in view, we synthesized a series of N'-(1-benzyl-2-oxo-1, 2-dihydro-3H-indol-3-ylidene) hydrazide derivatives and evaluated them in vitro for antiproliferative activities in MCF-7 (ER+) cell line. We further investigated the effect of the most potent compound (5i) on the Erα through Western Blot Analysis. We used in silico pharmacokinetics prediction tools, particularly pkCSM tool, to assess the activity profiles of the compounds. Results and discussion: Compound 5i showed the best antiproliferative activity (IC50 value; 9.29 ± 0.97 µM) in these cells. Furthermore, 5i downregulated ERα protein levels in a dose-dependent manner in MCF-7. A multifaceted analysis of physicochemical properties through Data Warrior software revealed some prominent drug-like features of the synthesized compounds. The docking studies predicted the binding of ligands (compounds) with the target protein (ERα). Finally, molecular dynamics (MD) simulations indicated stable behavior of the protein-ligand complex between ERα and its ligand 5i. Overall, these results suggest that the new isatin derivative 5i holds promise as a new ERα degrader.